Petrogenesis and geological significance of the Mesozoic granitoids in the Mangzhang-Jiucheng area, Tengchong terrane, Yunnan province: evidence from petrology, geochemistry and zircon U-Pb geochronology - Liu, Wei; Wu, Jinglong; Ruan, Yuelei; Gong, Chen; Shang, Yan; Chen, Geng; Liu, Yuan; Wu, Jialing; Li, Xiaojun; Wang, Xiaofeng; Kong, Xu; Mo, Xiong (Frontiers in Earth Science, 2025)
The Mangzhang-Jiucheng granitoids of the Tengchong Terrane offers critical insights into the Mesozoic tectono-magmatic evolution of the eastern Tethyan Tectonic Domain. LA-ICP-MS zircon U–Pb geochronology identifies two emplacement phases at 210.6–207.1 Ma and 121.4–118.7 Ma, recording Late Triassic and Early Cretaceous magmatic events with Ti-in-zircon crystallization temperatures of 531 °C–720 °C and 582 °C–816 °C, respectively. Geochemically, both the Late Triassic and the Early Cretaceous granitoids belong to acidic, peraluminous, exhibiting pronounced enrichment in LREE and large-ion lithophile elements (Rb, Th, U, La, Ce, Zr and Hf) and conspicuous depletion in high-field-strength elements (Nb and Ti) together with Sr, Ba and HREE. The Late Triassic granitoids exhibit S-type affinity, indicating that magma may source from meta-sedimentary materials. The Early Cretaceous granitoids exhibit predominantly S-type affinities and are derived from metasedimentary sources, and may have formed in volcanic-arc (VAG), syn-collisional (syn-COLG), or within-plate (WPG) tectonic settings. The Late Triassic granitoids may be related to the accretion of the Tengchong Terrane and the Indochina Block upon closure of the Paleo-Tethys Ocean (PTO), whereas Early Cretaceous granitoids may link to the subduction of the Meso-Tethys Ocean (MTO), accompanied by slab rollback, break-off and asthenospheric upwelling that associate with the final suturing of the MTO.